Phytoconstituents Analysis and In Vitro Antiproliferative Activity of Abrus precatorius Leaves on Cancer Cells - Wan Suriyani Wan Ibrahim; Siti Farhanah Mohd-Salleh; Harishini Rajaratinam; Nor Amalia Nazri; John Ogbaji Igoli; Nurkhalida Kamal; Norzila Ismail (Tropical Life Sciences Research, 2026)
Traditionally in Malaysia, the leaves of Abrus precatorius, a flowering plant that belongs to the legume family, Fabaceae, are used to treat various ailments such as coughs, diarrhoea, wound healing and even as anticancer and antivirus remedy. The study aimed to identify the phytocompounds present in A. precatorius leaves using (1) different solvents and (2) two different extraction methods for each solvent. Additionally, we have also intended to investigate the anti-proliferative activity of those maceration-based extracts on selected cancer and normal cell lines. In this study, two extraction methods were used (maceration and Soxhlet extraction), using sequential solvents according to their polarity, starting with hexane, ethyl acetate and methanol. The phytocompounds were identified via the GC-MS technique. The findings reported that the ethyl acetate extract (obtained via Soxhlet extraction) contained the highest amount of terpenoids, while the methanol extract (obtained via maceration) contained the highest combination of terpenoids and phenolic compounds. The triple negative breast cancer cell line, MDAMB-231 showed high sensitivity towards all A. precatorius leaf extracts (maceration-based). The hexane extract of A. precatorius leaves (maceration-based) showed the lowest IC50 on MDA-MB-231 cells at 80.75 ± 64.0 μg/mL. In conclusion, potential anticancer phytocompounds were identified in the A. precatorius leaves extracts such as 1-octacosanol, neophytadiene and 4-vinylphenol. All maceration-based extracts exhibited non-cytotoxicity effect on both normal breast cell MCF-10a and fibroblast cell NIH (3T3). The MDA-MB-231 cell line was the most sensitive towards all maceration-based extracts, particularly hexane-maceration based.